2004
DOI: 10.1007/s00425-004-1355-x
|View full text |Cite
|
Sign up to set email alerts
|

Inappropriate annotation of a key defence marker in Arabidopsis: will the real PR-1 please stand up?

Abstract: PR-1 has been extensively used as a marker for salicylic acid (SA)-mediated defence and systemic and local acquired resistance. The Arabidopsis Genome Project annotates At2g19990 as PR-1. This gene is also identified as PR-1 in two "full genome" Arabidopsis microarrays, and TAIR cites approximately 60 articles to describe its patterns of expression. However, most of these citations are incorrect; the probes used were not At2g19990, but a homologous gene At2g14610, which is annotated as "PR-1-like". Because of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 13 publications
1
29
0
Order By: Relevance
“…Furthermore, VSP2, whose transcript level is strongly decreased in response to exogenous ET (Rojo et al, 1999;Van Zhong and Burns, 2003), was up-regulated during K 1 starvation. Similarly, searching our data for known SAresponsive genes such as PR1-like (At2g14610; Uknes et al, 1992;Laird et al, 2004), PR5 (At1g75040), NPR1 (At1g64280; Cao et al, 1997), and WRKY18 (At4g31800; Yu et al, 2001) revealed no indication for increased SA production during K 1 starvation. Cross-talk between SA, JA, and ET has been modeled from gene expression data obtained from Pseudomonas syringae infected signaling-defective Arabidopsis mutants (using the Affymetrix 8K microarray; Glazebrook et al, 2003).…”
Section: Discussionmentioning
confidence: 87%
“…Furthermore, VSP2, whose transcript level is strongly decreased in response to exogenous ET (Rojo et al, 1999;Van Zhong and Burns, 2003), was up-regulated during K 1 starvation. Similarly, searching our data for known SAresponsive genes such as PR1-like (At2g14610; Uknes et al, 1992;Laird et al, 2004), PR5 (At1g75040), NPR1 (At1g64280; Cao et al, 1997), and WRKY18 (At4g31800; Yu et al, 2001) revealed no indication for increased SA production during K 1 starvation. Cross-talk between SA, JA, and ET has been modeled from gene expression data obtained from Pseudomonas syringae infected signaling-defective Arabidopsis mutants (using the Affymetrix 8K microarray; Glazebrook et al, 2003).…”
Section: Discussionmentioning
confidence: 87%
“…In the tumor, several genes involved in ET perception and signaling were activated. By contrast, genes involved in JA signaling, such as JAZ family members, COI1 (At2g39940; Katsir et al, 2008;Staswick, 2008), or MYC2 (At1g32640; Lorenzo et al, 2004) as well as the two classical marker genes of the SA-induced SAR response pathway, PR1 (At2g14610; Laird et al, 2004) and NPR1 (At1g64280), were never found to be activated. This observation suggests that the auxin and ET signaling pathways, rather than SA-induced SAR, seems to be induced in the host during Arabidopsis-Agrobacterium interaction.…”
Section: H 2 O 2 Accumulation Is Prevented At the Beginning Of The Inmentioning
confidence: 94%
“…Among the biochemical pathway and physiological function marker loci represented on our microarrays, transcripts coding for 4-coumarate-CoA ligase (4-CL), chalcone isomerase (CHI), NADPH-dependent P450 reductase (ATR3), glyceraldehyde 3-P dehydrogenase A (GapA), copper/zinc superoxidase dismutase (CSD1), vegetative storage protein (Vsp1), Asn synthetase (ASN1), and a number of other loci were expressed higher in the Col ecotype. In contrast, only transcripts coding for cytochrome b 5 , a pathogenesisrelated 1 (PR1)-similar protein, and two other unassigned proteins were expressed higher in the Ler ecotype; the PR1-similar transcript is related to the plant defense protein expressed in response to pathogen infection and treatment with resistance-inducing compounds (Laird et al, 2004).…”
Section: Transcript Profiling In Col and Ler Ecotypesmentioning
confidence: 98%